Hadith #4223 - Sunan Abi Dawud - Hassan ibn Ali bin Abi Talib; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Nwh bin Rabi'ya al-Ansari نوح بن ربيعة الأنصاري مولاهم أبو مكين; Sahl bin Hamad سهل بن حماد (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and he was wearing a signet-ring of yellow copper. He said to him: How is it that I notice the odour of idols in you? So he threw it away, and came wearing an iron signet ring. He (the Prophet) said: What is it that I see you wearing the adornment of the inhabitants of Hell? So he threw it away. He asked: Messenger of Allah, what material I must use? He said: Make it of silver, but do not weigh it as much as a mithqal, The narrator Muhammad did not say: ” ‘Abd
Grade: Hasan